1994
DOI: 10.1093/ajcn/59.1.185s
|View full text |Cite
|
Sign up to set email alerts
|

Assessing change in diet-intervention research

Abstract: In nutrition-intervention research, it is important to consider the sensitivity of dietary assessment instruments to the changes in nutrient intake or dietary behavior under study. This presentation describes a measure called "responsiveness," an index of an instrument's sensitivity to change. Illustrations of this measure are from two randomized dietary-intervention trials that targeted reductions in fat intake: the Women's Health Trial (WHT), a trial to test whether fat reduction would reduce the risk of bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
113
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(115 citation statements)
references
References 9 publications
1
113
0
1
Order By: Relevance
“…Table 2 shows the correlations between the dietary and exercise subscales and criterion variables. For dietary comparisons, criterion measures were derived from 3-or 4-day food records, food-frequency questionnaires (42,44), the Food Habits Questionnaires (45), and the Block Fat Screener (46). For exercise, comparisons were with the Stanford 7-Day Recall (47), the Physical Activity Scale for the Elderly (48), exercise self-monitoring data (33), or attendance at an exercise class.…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 shows the correlations between the dietary and exercise subscales and criterion variables. For dietary comparisons, criterion measures were derived from 3-or 4-day food records, food-frequency questionnaires (42,44), the Food Habits Questionnaires (45), and the Block Fat Screener (46). For exercise, comparisons were with the Stanford 7-Day Recall (47), the Physical Activity Scale for the Elderly (48), exercise self-monitoring data (33), or attendance at an exercise class.…”
Section: Discussionmentioning
confidence: 99%
“…Although the validity and reproducibility of the FFQ used in this study have been demonstrated, its ability to quantify changes in intake over long times has not been established. The FFQ approach has been found to be only slightly less responsive than multiple diet records in determining changes in fat intakes in an intervention study (Kristal et al, 1994), indicating that the FFQ is able to measure change and, if anything, tends to underestimate change in dietary intake. Another limitation of this study is the absence of a time-sequential component, that is, recruitment of a new group of adults aged 70 y and older in 1995a96, for the examination of time effects.…”
Section: Discussionmentioning
confidence: 99%
“…36 Fruit/vegetable and sweets intake were selected as the nutritional measures because fruit and vegetable consumption has been identified as a proxy for an overall healthy diet, 28,29 and sweets have been considered a calorie-dense, nutrient-poor, and unhealthy food type. 30,31 Because of its applicability for field research, 45 and based on previous guidelines 46 and applications, 35 single items enabled recall of daily intakes of servings of fruits (eg, 1 small pear, 118 mL of fruit either canned or as juice), vegetables (eg, 118 mL of peas or carrots, 236 mL of raw spinach), and sweets (eg, 1 small piece of chocolate candy [~ 30 mL], 1 small piece of cake [~ 59 mL]). These corresponded to the current U.S. Department of Agriculture's Food Plate, and its earlier Food Guide Pyramid.…”
Section: Methodsmentioning
confidence: 99%